Isolation of poly(3-hydroxybutyrate) from bacterial biomass using soap made of waste cooking oil - Pospisilova, Aneta; Novackova, Ivana; Prikryl, Radek (Bioresource technology, 2021)
The aim of this work was to develop a soap-based method for the isolation of poly(3-hydroxybutyrate) from bacterial biomass. The method consisted of adding soap derived from waste cooking oil to a concentrated (25%) biomass suspension, heating and centrifugal separation. Purity above 95% could be achieved with soap:cell dry mass ratios at least 0.125 g/g, making the method comparable to other surfactant-based protocols. Molecular weights Mw of products from all experiments were between 350 and 450 kDa, being high enough for future material applications. Addition of hydrochloric acid to the wastewater led to the precipitation of soap and part of non-P3HB cell mass. The resulting precipitate was utilized as a carbon source in biomass production and increased substrate-to-P3HB conversion.
Keywords: Hydroxybutyrates; Soaps; polyestery; Bioreactors; hydroxybutyráty; Cooking; Downstream process; Biomass; Isolation; vaření; 3-Hydroxybutyric Acid; PHA; kyselina 3-hydroxymáselná; biomasa; Polyesters; bioreaktory; P3HB; Recovery; mýdla